Indigenous bacterial diversity and identification in domestic wastewater in small tropical island - Sukmawati; Birawida, A. B.; Ambeng; Sham, S. M.; Sumarheni (GJESM Publication, 2026)
BACKGROUND AND OBJECTIVES: Domestic wastewater discharge in small island communities is a major environmental and public-health concern due to the absence of centralized treatment and direct release of effluents into coastal waters. These circumstances encourage microbial contamination, nutrient enrichment, and ecological imbalance, heightening the risk of waterborne diseases and adversely affecting coastal ecosystems. In the small islands of Indonesia, the restricted land availability and dependence on nearby waters heighten their susceptibility. Rasing the dynamics of local microbial communities is vital to inform sustainable wastewater management and enhance nature-based bioremediation appropriate for resource-limited islands. METHODS: Wastewater samples were collected from three household discharge points on a small tropical island in Indonesia during the dry season. Indigenous bacterial isolates suitable for culturing were obtained via standard microbiological procedures and characterized through morphological, biochemical, and physiological evaluation. Molecular identification was performed using 16S ribosomal ribonucleic acid gene sequencing to achieve species-level resolution and phylogenetic placement. The concentration on culturable bacteria was directed towards native strains with the potential for immediate use in cost-effective, community-oriented treatment systems. FINDINGS: Six bacterial species were identified: Escherichia coli, Pseudomonas aeruginosa, Enterobacter cloacae, Vibrio alginolyticus, Klebsiella pneumoniae, and Bacillus subtilis. These isolates tolerated salinity from 5 to 10 percent, temperature from 15 to 45 degrees Celsius, and hydrogen-ion concentration from 6 to 9, showing adaptability to coastal wastewater. Their metabolic features point to their potential as indigenous microbial resources for nature-based solutions in small island environments. The presence of potentially pathogenic species such as Escherichia coli, Klebsiella pneumoniae, and Vibrio alginolyticus underscores the threat of waterborne disease transmission in communities discharging untreated wastewater, highlighting the importance of developing treatment approaches that are adapted to local needs to ensure public health and environmental quality. CONCLUSION: This study provides baseline evidence of the ecological versatility and taxonomic diversity of indigenous bacteria in small-island wastewater. The outcomes advocate for the establishment of consortium-oriented, cost-effective, sustainable bioremediation strategies that correspond with the United Nations Sustainable Development Goal 6 on Clean Water and Sanitation. These insights highlight the importance of integrating microbial evidence into local wastewater-management policies. They also advocate for research focused on the performance of pollutant-removal effectiveness, the biosafety of potentially pathogenic strains, and long-term ecological monitoring essential for ensuring safe and resilient applications in small island settings.